Peranan Elemen Desain Interior Dalam Membentuk Atmosfer Ruang Tunggu CIP Lounge Bandara - Rr. Chandrarezky Permatasari; Nuarista Edi Nugraha (Pascasarjana Institut Seni Indonesia Surakarta, 2020)
The atmosphere of the space can be formed visually through its interior design elements. In this study shows how the role of interior design elements is applied to the public waiting room in CIP Mandiri Priority Lounge Kualanamu conducted to determine the atmosphere of the atmosphere that forms the image of corporate lounge image.The existence of a space formed through the physical elements of interior design consisting of horizontal and vertical elements. This basic element is present along with the color, light, texture and pattern of the field which will affect the perception of visual weight, proportion and dimensions. Other non-physical elements of a space are socio-cultural elements carried by other people and the environment can affect interactions in the form of non-physical elements of a space.The physical and non-physical elements work together to create the atmosphere of a space that has characteristics that are able to build a space image.This research uses a qualitative method with a descriptive analysis approach. Data collection techniques through survey studies. From the analysis of the data it was found that the role of the interior design elements forming the space greatly influences the atmosphere of the public lounge CIP lounge in accordance with the image of identity of a lounge. The character of the atmosphere formed is linked and assessed for its suitability to the style, function of the area in the Airport CIP Lounge